Contribution of Grape Juice to Develop New Isotonic Drinks With Antioxidant Capacity and Interesting Sensory Properties - Bendaali, Yasmina; Vaquero, Cristian; González, Carmen; Morata, Antonio (Frontiers in Nutrition, 2022)
Nowadays, the sector of isotonic beverages has developed its market based on fruit juices which provide a sports drink with antioxidant and biological activities in addition to their principal role of rehydration and replacement of minerals and carbohydrates during physical exercise. The consumption of grape juice is increasing worldwide because of its sensory characteristics and nutritional value. It contains mainly water, sugars, organic acids, and phenolic compounds. The phenolic compounds play a major role in the prevention of various diseases through their biological activities linked to antioxidant, anti-inflammation, anticancer, antiaging, antimicrobial, and cardioprotective properties. Several studies have demonstrated that grape juice is able to improve performances of antioxidant activity, protect against oxidative damage and reduce inflammation during sports activities. Polyphenol content also provides a great sensory profile, mainly color which is an important indicator for consumers when choosing beverage products. The contribution of grape juice through its nutritional value and sensory properties make it an alternative for the development of a new isotonic drink which will be a novel and healthy product in the field of the healthy beverages.